Anti-Smoking Campaign to Increase Public Awareness in Betoambari Regency - Didin Halim; Zarni Adia Purna; Muh Arifai; Yusri Karmila; Muh Asdar (Jurnal Pengabdian Masyarakat Al-Fatimah, 2024)
The anti-smoking campaign in Betoambari District is an effort to increase public awareness of the dangers of smoking and reduce the prevalence of smoking in the area. Through a series of stages of preparation, implementation, and evaluation, this campaign has achieved significant impact. The survey results show an increase in public awareness of the health risks caused by smoking, as well as a decrease in smoking prevalence among residents. The success of this campaign is supported by the effectiveness of its messages, which are informative, relevant, and attract attention, as well as the important role of mass media and community activities in spreading anti-smoking messages. To ensure the sustainability of the program, ongoing measures such as regular counseling, educational campaigns in schools, and the formation of anti-smoking communities are important. In conclusion, this anti-smoking campaign has made a significant contribution to increasing public awareness and reducing the prevalence of smoking in the Betoambari District, with the hope of continuing to have a long-term positive impact on the health of the local community.